ACCURATE AND COMPUTATIONALLY EFFICIENT THREE DIMENSIONAL NONLINEAR MODEL FOR THE ANALYSIS OF LARGE-SCALE RC STRUCTURES SUBJECTED TO CYCLIC & DYNAMIC LOADING CONDITIONS - Mourlas, Christos (My University, 2018)
The analysis of reinforced concrete structural members is characterized by heavy nonlinearity which is mainly caused by the cracking of the material. The complex cyclic and dynamic behavior of concrete makes the numerical procedure even more difficult to converge and provide accurate results. The constitutive models that are proposed in the literature, try to describe the mechanical characteristics of the RC structural members through idealized constitutive laws based on plasticity theory, thermodynamic laws and fracture mechanics. The lack of their objectivity derives from the need of introducing many new material parameters and energy functions in order to capture the experimental behavior of concrete (like all models they sometimes manage to capture the mechanical behavior of concrete and some others they fail to do so). Many of these parameters (derived from the thermodynamic framework) do not have physical interpretation and their values changes significantly when different mechanical behaviors of RC structures take place. In addition, these models present many numerical instabilities which make it difficult to use them for cyclic or dynamic analysis and therefore they are unable to use them for modelling full scale RC structures. Another weakness of the models found in the literature, is the use of uniaxial constitutive relations. This explains the use of parameters that introduce triaxial characteristics, such as plasticity, effect of confinement, triaxial crushing and interaction between compressive and tensile stresses in the concrete members. Therefore, the constitutive model of concrete has to be constructed based on: • Triaxial behavior of concrete • Brittle nature of concrete Therefore, the main objectives of the current work are summarized by the following: • Develop a constitutive model which can describe the triaxial and brittle behavior of concrete without adding new material parameters with no physical interpretation. • The model has to be incorporated in a 3D detailed FEM model. • The numerical procedure has to model the effect of cracking and material deterioration accurately. • Discrete modelling of steel reinforcement as embedded rebars. • Accurate modelling of steel reinforcement as concerned the exact location inside hexahedral concrete elements and uniaxial constitutive behavior. • Validate the proposed model by comparing experimental results for structural members submitted to static monotonic and cyclic loading conditions. • Extend the proposed numerical model, in order to model accurately full scale structures under static monotonic and cyclic loading conditions. • Validate the proposed model by comparing experimental results for structures submitted to dynamic loading conditions. • Provide the analysis with computational efficiency that the analysis can be carried out after a logical amount of iterations and during a logical amount of time. Furthermore a computer with standard basic characteristics can perform these analysis. • Use the numerical results for practical interest as concerned the seismic response of RC structures, such as, testing different retrofitting techniques or various retrofitting configurations.
Keywords: Numerical Modeling; Reinforced Concrete; Cyclic Loading; Nonlinear Analysis; Seismic Assessment; Material Constitutive Modeling; Dynamic Analysis